PENGARUH HARGA DIRI TERHADAP KECENDERUNGAN PERILAKU SELF INJURY PADA SISWA SMP NEGERI DI KECAMATAN TEMBALANG TAHUN PELAJARAN 2019/2020 - Nadia Rachma Putri; Eko Nusantoro (Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry, 2020)
This study aims (1) to know the level of self-esteem, (2) to know the tendency of self-injury behavior, and (3) to find out the effect of self-esteem on the tendency of self-injury behavior in state junior high school students in Tembalang District. The approach used in this study is a quantitative approach to the type of correlational research. Data collection techniques used were psychology scale with 24 items self-esteem scale instrument and 34 items self-injury behavior tendency scale. The population in this study were students of class VIII and XI state junior high school in Tembalang District with a total sample of 187 students who were determined purposively. Data analysis techniques used (1) quantitative descriptive analysis to describe the level of self-esteem and the tendency of self-injury behavior in students, (2) hypothesis testing with product moment analysis to determine the effect of self-esteem on the tendency of self-injury behavior. The results showed that self-esteem influences the tendency of self-injury behavior.